2006
DOI: 10.1007/s00114-006-0185-z
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variations in seed dispersal by ants: are plant and seed traits decisive?

Abstract: The effect of local ant species on the dispersal success of a myrmecochorous plant, Helleborus foetidus, was analyzed in two populations of the Iberian Peninsula (Caurel and Cazorla, respectively). The contribution of the various local ant species to dispersal was very unequal. While 5 and 19 ant taxa visited the plants of Caurel and Cazorla, respectively, most removal activity (67 and 80%) was performed by two species only (Formica lugubris and Camponotus cruentatus, respectively). Visits by dispersers were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 22 publications
0
38
0
1
Order By: Relevance
“…The foraging decicions of A. rudis may only be responsive to a wider range of seed or elaiosome sizes. Other studies have also found that size does not completely predict removal [46], [47].…”
Section: Discussionmentioning
confidence: 87%
“…The foraging decicions of A. rudis may only be responsive to a wider range of seed or elaiosome sizes. Other studies have also found that size does not completely predict removal [46], [47].…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, variation in the relative concentration of fatty acids between individuals may have important ecological consequences, like has recently been proposed for Helleborus foetidus. In that plant species, Boulay et al (2007) found that the frequency of visits to plants by ant dispersers (and consequently seed removal) was highly correlated with interindividual differences in oleic acid content of elaiosomes. Thus, the chemical composition of elaiosomes seems to be under strong selection by ants and may indirectly play an important role in determining local plant demography.…”
Section: Discussionmentioning
confidence: 96%
“…Among lipids, fatty acids are major components of elaiosomes and a few of these compounds (e.g., oleic or oleyl-based glycerides) have been identified as mainly responsible for elaiosome attractiveness by ants (Brew et al, 1989;Marshall et al, 1979;Skidmore and Heithaus, 1988). Consequently, some studies have focused in assessing the fatty acid composition of elaiosomes of a plant species, occasionally drawing interspecific comparisons on fatty acid profiles (Lanza et al, 1992;Mackay and Whalen, 1998;Pfeiffer et al, 2010;Soukup and Holman, 1987), but only a few of them have assessed the effects of natural variation in the fatty acid profile within species (Boulay et al, 2006(Boulay et al, , 2007.…”
Section: Introductionmentioning
confidence: 97%
“…The internal organs are rich in long-chain fatty acids derived from triglycerides and cholesterol. Fatty acids that are derived from seed elaiosomes are also used as rewards and/or semiochemicals that help trigger seed-dispersal behavior of ants (26,27). These behaviors indicate that ant antennae are able to detect fatty acids.…”
Section: Cjapnpc2 Carries Hydrophobic Semiochemicals Evoking Antennalmentioning
confidence: 99%